Объяснение:
а) Pb(NO3)2 + Na2S = PbS↓ + 2NaNO3
Pb(2+) + 2NO3(-) + 2Na(+) + S(2-) = PbS↓ + 2Na(+) + 2NO3(-)
Pb(2+) + S(2-) = PbS↓
б) Na2SO4 + 2AgNO3 = Ag2SO4 ↓+ 2NaNO3
2Na(+) + SO4(2-) + 2Ag(+) + 2NO3(-) = Ag2SO4↓ + 2Na(+) + 2NO3(-)
2Ag(+) + SO4(2-) = Ag2SO4↓
в) 3Ba(NO3)2 + Al2(SO4)3 = 3BaSO4↓ + 2Al(NO3)3
3Ba(2+) + 6NO3(-) + 2Al(3+) + 3SO4(2-) = 3BaSO4↓ + 2Al(3+)+ 6NO3(-)
Ba(2+)+ SO4(2-) = BaSO4↓
г) Cu(OH)2 + 2HNO3 = Cu(NO3)2 + 2H2O
Cu(OH)2 + 2H(+) + 2NO3(-) = Cu(2+) + 2NO3(-)+ 2H2O
Cu(OH)2 + 2H(+) = Cu(2+) + 2H2O
е) Ca3(PO4)2 + K2CO3 реакция не пойдёт
ж) AgNO3 + HCl = AgCl↓ + HNO3
Ag(+) + NO3(-) + H(+) + Cl(-)= AgCl↓ + H(+) + NO3(-)
Ag(+) + Cl(-) = AgCl↓
1) 4Ca + 10HNO3=4Ca(NO3)2+5H2O+N2O
4Ca+10H+10NO3=4Ca + 8NO3 +5H2O+N2O
10H+10HO3=8NO3+5H2O+N2O
2) Ca(NO3)2 + Na2CO3 = CaCO3 + 2NaNO3
3) CaCO3=CaO+CO2
4) CaCO3+CO2+H2O=Ca(HCO3)2